Blood ties - Nix, Garth; Williams, Sean, 1967- (New York, NY : Scholastic Inc., 2014)
As the Conquerors try to destroy Erdas, Meilin -- fed up with waiting and ready to fight -- sets off into enemy territory with her spirit animal, a panda named Jhi. Her friends Conor and Abeke aren't far behind ... but they're not the only ones.
Keywords: Human-animal relationships -- Juvenile fiction; Good and evil -- Juvenile fiction; Shapeshifting -- Juvenile fiction; Human-animal relationships -- Fiction; Good and evil -- Fiction; Shapeshifting -- Fiction; Fantasy; Good and evil; Human-animal relationships; Shapeshifting; Fiction; Juvenile works; Fantasy fiction